An Opportunities-Based Approach to Mitigating Risks Associated with Infrastructure Development Projects - Messerschmidt, Don (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
‘Risk' is a major point of focus in the literature on resettlement and reconstruction associated with the impacts of major infrastructure development on project affected individuals and families. Previous approaches to risk appear to emphasize the negative consequences of development, and it is no wonder then that project affected people often emphatically resist development and change. This paper proposes that a more pro-active, positive opportunities and benefits approach be taken in dealing with resettlement and reconstruction associated with large scale infrastructure projects. The discussion is focused on the eight ‘risk factors' (or ‘opportunity factors'?) listed in the well known ‘Impoverishment Risk and Reconstruction' (IRR) Model. Three more such factors are added to the list based on field experience in South Asia. The point is that by emphasizing the potential opportunities and benefits, project affected people are more likely to be supportive of projects that may disrupt their lives. Key words: Resettlement, opportunities, risk, IRR model, South Asia, infrastructure development doi: 10.3126/hn.v3i0.1912 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 9-15